Analisis Rasio Keuangan Dan Metode Economic Value Added (EVA) Untuk Menilai Kinerja Keuangan Perusahaan - Ahmad Irfan Nurhakim; Raden Aditya Kristamtomo (Journal of Economic, Bussines and Accounting (COSTING), 2021)
State-owned enterprises (BUMN) liquid a form of government investment that manages the life of many people, state-owned construction (KARYA) liquid state-owned enterprises that focus on the field of considerable construction is very influential in all aspects of the country. Entering the era of globalization and the demands of construction services users to the company's performance permissible better. The very strict competition between construction companies can pose a risk of competition in the financial performance of state-owned enterprises (KARYA), so that state-owned enterprises are still weak in the mastery of local project (market). This research aims to identify financial performance in the STATE of construction (KARYA) from the level of liquidity, solvency, and profitability and examined by the economical value-added method (EVA) to know the value added economy in the company'S construction Field (KARYA). This method of study uses a quantitative descriptive method with the approach of financial analysis and the use of economic value-added methods (EVA). Using data will be financial from Tofu 2015 S. D 2018. Based on the results of the analysis of financial performance of the 4th (four) enterprises in the work in the field of poor debt acquisition is a major factor and added economic value shows less good results because fewer companies obtain positive value. This should be the company to maintain liquidity ratio value.. Keywords: Financial Ratio Analysis, Economic Value Added, BUMN Construction